Republic and conservative catholicism - Aljovín de Losada, Cristóbal (2020)
This work aims to explain the different ways of conceiving Republicanism among catholic conservatives in Colombia, Ecuador and Peru, by comparing these republics during the Nineteenth Century. The focus of the study is to connect the conflicting relationship between religion and politics through a discussion on the so-called “catholic republic”, in opposition to the republican model envisioned by liberals and radicals. The role of the Catholic Church in the modern world was a central concern for conservatives who wanted to insert the American reality in the wider context of the “catholic civilization”, which served as a point of connection for the catholic community and the political modernity. This insertion was not easy. The political conflicts as a result of this ideological discussion will become more apparent during the second half of the Nineteenth Century. In some cases, reaching high levels of political violence. In this article, we will concentrate in three aspects of the discussion that we regard as central: the idea of nation, the religious tolerance and the education.